Security System Implementation And Monitoring Networks At Sma N 10 City Of Bengkulu - Refki Iqromullah; Khairil Khairil; Eko Suryana (Jurnal Media Computer Science, 2023)
One of the systems to be able to carry out network security and monitoring can use a firewall and Graphana with the Ubuntu Server Linux operating system. In running the security system and monitoring the network using a firewall and Graphana it is supported by several other tools or applications such as Apache2, PHP and MySQL. So by using a security system and network monitoring can use a firewall and grafana can monitor and network security, where every activity in accordance with the settings given is carried out by grafana, then from the monitoring results an analysis will be carried out which activities are allowed and which are not allowed. Furthermore, from the results of this analysis, restrictions will be made using a firewall. Linux ubuntu server 20.04 is an open source operating system, the Linux ubuntu server 20.04 operating system is very good as a server for running security systems and monitoring networks, you can use firewalls and graphana because it doesn't require high hardware specifications and can also be obtained free of charge because it is open. sources.